Answer:
267
Step-by-step explanation:
We are given the expression: 6 (d - f) +f
The value of the expression when d= 47 and f = 3 is :
6 (47 - 3) +3 = 6×(44) + 3 = 264 + 3 = 267
=267
Answer:
f(5) = 13
General Formulas and Concepts:
<u>Pre-Algebra</u>
- Order of Operations: BPEMDAS
<u>Algebra I</u>
- Function notation and substitution
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = x² - 12
x = 5
<u>Step 2: Evaluate</u>
- Substitute: f(5) = 5² - 12
- Exponents: f(5) = 25 - 12
- Subtract: f(5) = 13